Strategies for Strengthening the Economic Resilience of Small Industries - Juliana, Juliana; Saputro, Guntur; Suwito, Suwito (PPSDP International Journal of Education, 2025)
This research examines government strategies in strengthening the small industrial economy or MSMEs to enhance economic resilience. This research uses a literature study method. It uses the defense strategy theory introduced by Arthur F. Lykke, which includes the aspects of way, means, and end. The research results show that, from the ‘way’ aspect, the government, through the RPJMN 2020 - 2024, has committed to strengthening entrepreneurship and MSMEs through five priority areas: developing human resources (HR), increasing access to financial services, increasing the added value of MSME products in domestic and international markets, strengthening partnerships, and improving regulations and policies affecting MSME sustainability, some of which have not been fully implemented by the government. From the ‘means’ aspect, existing resources have not been optimally utilized by the government, such as the empowerment of human resources, which has not been optimal.